The Role of Government in Awarding Outstanding Student Athletes in West Bandung Regency - Rudiawati, Winda; Nuryadi, Nuryadi; Gumilar, Agus (JUMORA: Jurnal Moderasi Olahraga, 2024)
Awards are a form of appreciation for the efforts and achievements of student athletes who have brought pride to their region. Sports are one of the benchmarks of success, both for athletes, regions, and countries. In addition, sports also reflect good cooperation between the government and the community. Athletes' achievements do not happen by chance but require full attention and support from the government. A survey was conducted on sports administrators in the West Bandung Regency area with 45 respondents. Based on the analysis, policy implementation and budget management have a significant influence on the expected success. Awards have been proven to motivate athletes, especially if given consistently and on time. Although the government has tried to improve the quality of awards every year, there are still many things that need to be improved, especially related to adequate support and training